Adherence to therapeutic and diagnostic recommendations in patients with femur fracture and at risk of re-fracture or death: results of an analysis of administrative databases - C. Veronesi; C. Magliaro; C. Cagnoni; S. Adami; M. Rossini; L. Sinigaglia; L. Degli Esposti; S. Buda; S. Minisola (PAGEPress Publications, 2012)
The aim of the present study was to evaluate the application into clinical practice of therapeutic and diagnostic recommendations for the prevention of bone re-fracture in postmenopausal women after an hospitalization for hip fracture in clinical practice and to assess the relationship between the application of diagnostic recommendations and re-fracture or death risk. A retrospective cohort analysis was conducted. All female patients, at least 65 years old, and with an hospitalization with main or secondary diagnosis of hip fracture during the period 1 January 2006 - 31 December 2008, were included. Besides demographic characteristics and comorbidities, drug treatment prescriptions related to bone fracture or supplementary with calcium or vitamin D and prescriptions of recommended laboratory and instrumental diagnostic tests (e.g. spine radiography), were analysed. A total of 5,636 patients were included in the study. The prescription of a drug treatment aimed to reduce the risk of re-fracture was found in 16.3% of patients, among them 76.3% (699 patients) used bisphosphonates only, 17.1% (157 patients) strontium ranelate only and 4.9% (45 patients) used more than one treatment during the observation period. Among the patients who did not receive drug treatment, 17.5% made use of only supplemental calcium and vitamin D. The remaining part of patients (69.1%) received no treatment. The prescription of at least one laboratory test of first and second level was performed, respectively, on 53.7% and 43.1% of included patients, whereas the prescription of at least one instrumental test of first and second level was performed, respectively, on 5.9% and 0.8%. Although it is established that the prescription of the recommended tests and appropriate drug treatment are significantly associated with reduced risk of re-fracture and death, today the application of these recommendations is reduced.